Relationship between virulence factor and toxin antitoxin system in enterococcus - Soheili, Sara (2014)
Toxin-antitoxin system is a regulatory system where two sets of genes encodes the toxin and its corresponding antitoxin. There is no documented study that showed the association between virulence genes and TA system in Enterococcus faecium and Enterococcus faecalis. For this purpose,the prevalence of TA systems in independently isolated clinical isolates of E. faecium and E. faecalis were determined, then the dominant TA systems were identified, different virulence genes in E. faecium and E. faecalisare surveyed and subsequently the level of expression of virulence and TA genes in normal and stress conditions were determined and finally their association with TA genes are defined.Remarkably, sequences for one particular TA pair, mazEF and higBATA systems, were present on plasmid and chromosome of all E. faecium andE. faecalis strains, respectively. Additionally, toxin transcript expression levels were increased when bacteria were grown under stressful conditions. The pilB, fms8, efaAfm and sgrA are the most prevalent virulence genes in E. faecium and E. faecalis. These virulence genes were reported for first time in E. Faecalis, so this study demonstrated the importance of horizontal transformation in E. faecium and E. Faecalis. Peptide nucleic acid assay demonstrated with silencing of mazF by anti-mazF PNA a decrease of expression level of virulence genes were observed. The findings showed association between TA systems and virulence factor. The mazEF TA locion plasmid and higBA TA genes on chromosome of all E. faecium and E. faecalis were dominant. Also, there was decreasing of expression of virulence genes in presence of anti mazF-PNA. Therefore, it is recommended that mazEF TA systems are potent and sensitive targets in of all E. faecium and E.Faecalis. Hence, deactivation of the toxin proteins in the mazEF TA system should be investigated further as an effective antibacterial strategy against this bacterium.